2020
DOI: 10.4069/kjwhn.2020.10.28
|View full text |Cite
|
Sign up to set email alerts
|

The effects of health care programs for gestational diabetes mellitus in South Korea: a systematic review

Abstract: The purpose of this study was to investigate the effects and characteristics of health care programs for pregnant women with gestational diabetes mellitus (GDM) in Korea. This study was conducted according to the Cochrane Collaboration’s systematic literature review handbook and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guideline. We searched eight international and domestic electronic databases for relevant studies. Two reviewers independently selected the studies and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…의 임산부들을 대상으로 3일 동안 30분씩 중재군에게 지압을 적용 한 효과를 측정하였더니, 임산부의 불안도와 그 심각도가 유의하게 감소하였다 [27]. [34,35], 거구증 [34,36], 혈당 감소 [11,37], 우울 [11,36]…”
Section: ) 보완요법unclassified
“…의 임산부들을 대상으로 3일 동안 30분씩 중재군에게 지압을 적용 한 효과를 측정하였더니, 임산부의 불안도와 그 심각도가 유의하게 감소하였다 [27]. [34,35], 거구증 [34,36], 혈당 감소 [11,37], 우울 [11,36]…”
Section: ) 보완요법unclassified
“…Education programmes for pregnant women with GDM aiming to strengthen self-care are needed [ 13 ]. The present study aimed to assess the effectiveness of a tailored-care education programme on maternal and neonatal outcomes in pregnant women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to implement face-to-face education programmes for this population. According to the literature, different interventions were carried out to manage GDM [ 9 , 13 - 18 ]. Most of them were information technology (IT) programmes such as mobile health using smartphone applications X 18 , 19 ], educational digital optical disc (DVD) [ 11 ], and web-based programmes [ 9 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many intervention studies have been conducted for high-risk pregnant women. However, those studies mainly focused on changes in physical health indicators [10][11][12], including reductions in blood pressure [12], improvement of blood glucose levels [13], postpartum weight loss [11], and lowering of blood glucose levels in newborns [14]. Most systematic reviews of intervention studies on pregnant women with PTL only confirmed the treatment effect by applying drugs, tests, or treatment guidelines to prevent premature birth [10,15,16].…”
Section: Introductionmentioning
confidence: 99%